The impact of interest rate changes on Islamic bank financing - Abdul Kader, R.; Yap, K.L. (2008)
This study investigates the impact of interest rate changes on the demand for Islamic financing in a dual banking system where Islamic financing is dominated by Bai Bithamin Ajil (BBA) asset financing which replicate conventional bank loans. Using monthly data from 1999 to 2007, the study found that Islamic residential property financing exhibits a positive and fairly significant response to a shock in conventional residential property loans. This would imply a substitution effect. However, the response is not immediate and takes place only after one month. A possible explanation for this slow reaction is that, because BBA financing rate is fixed customers need time to reach a decision on whether or not to obtain financing from the Islamic bank based on their expectations of future interest rates movements. It is also found that unlike conventional bank residential property loans, Islamic residential property financing seems to respond more readily to a shock in the BLR. This again suggests that given the fixed rate of BBA financing, any change in the base lending rate would influence customers’ decision in obtaining Islamic bank asset financing. Overall, the study concludes that the structural weakness of the fixed BBA mechanism exposes Islamic banks in a dual system to risks of interest rate movements. This study therefore proposes that Islamic banks detach themselves from fixed rate instruments and move into more profit sharing financing. A viable alternative would be the property financing facility under musyarakah mutanaqisah.